Batteries for Electric Vehicles : Materials and Electrochemistry - Berg, Helena (Cambridge : Cambridge University Press, 2015)
This fundamental guide will teach you the basics of battery design for electric vehicles. Working through this book, you will understand how to optimise battery performance and functionality, whilst minimising costs and maximising durability. Beginning with the basic concepts of electrochemistry, the author moves on to describe implementation, control and management of batteries in real vehicles, with respect to the battery materials. The author describes how to select cells and batteries with explanations of the advantages and disadvantages of different battery chemistries, enabling you to put your knowledge into practice and make informed and successful design decisions, with a thorough understanding of the trade-offs involved. The first of its kind, and written by an industry expert with experience in academia, this is an ideal resource for both students and researchers in the fields of battery research and development as well as for professionals in the automotive industry extending their interest towards electric vehicles.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).